Tumbuhan dalam Ruang Budaya: Studi Etnobotani Pemanfaatan Tumbuhan pada Ritual Wiwit Kopi Masyarakat Wonosalam, Jombang - Dewi Tatum Rona Qotrun Nada; Faridatun Nafisah; Misfalah Arum Syandana; Reva Aulia Rahmadani; Fahrul Ghani Muhaimin; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to identify, analyze, and document the use of plants in the Wiwit Kopi ritual in Segunung Traditional Village, Wonosalam District, including plant species, habitus, organs used, methods and stages of use, philosophical meaning, and conservation efforts. This study uses a qualitative descriptive approach with data collection techniques in the form of non-participatory observation, documentation, and semi-structured interviews. The determination of informants was carried out using a purposive sampling technique for one key informant and a snowball sampling technique for three additional informants. Data analysis consists of data condensation, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results showed that there were 21 plant species from 14 families used in the Wiwit Kopi ritual with a dominant herbaceous habitus of 57.1%. The most commonly used plant organ was the leaf at 19.0%, while the conservation status category was dominated by Not Evaluated (NE) at 66.7%. The most prominent findings indicate that the use of plants in the Wiwit Kopi ritual not only serves as a complement to the ritual but also represents philosophical values ​​and supports culturally based conservation through the use of local plants passed down through generations.